2016
DOI: 10.12816/0032665
|View full text |Cite
|
Sign up to set email alerts
|

Incentives System for Nurses in Assiut University Hospital

Abstract: Background: Incentives play an important role in organizations as it influences a variety of work-related behavior, as well as the motivation of employees. Aims of the study: The present study was conducted in the main Assiut University Hospital to assess nurse's awareness and satisfaction regarding the incentives system. Subjects and Methods: This study included 271 nurses who randomly selected from all units at the main Assiut University Hospital. The study included both quantitative and qualitative methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study showed a high percentage of the respondents reported that fair remuneration, bounces, appropriate working hours and different services (health/ education) are the most important incentives respectively and the promotion, appreciation of work efforts, good relations with colleagues and superior encouragement were the most important incentives respectively. Furthermore, about half of the participants, especially female nurses, considered the moral incentives are more important than the financial one, especially the good dealing and respect from the physicians (6) .…”
Section: Khalek Et Al (2016) Discuss the Topic Of "Incentives Systemmentioning
confidence: 99%
“…The study showed a high percentage of the respondents reported that fair remuneration, bounces, appropriate working hours and different services (health/ education) are the most important incentives respectively and the promotion, appreciation of work efforts, good relations with colleagues and superior encouragement were the most important incentives respectively. Furthermore, about half of the participants, especially female nurses, considered the moral incentives are more important than the financial one, especially the good dealing and respect from the physicians (6) .…”
Section: Khalek Et Al (2016) Discuss the Topic Of "Incentives Systemmentioning
confidence: 99%